ARCHITECTURAL AND DESIGN MEANS OF FORMING THE FIRST IMPRESSION OF THE INTERIOR OF CULTURAL AND PUBLIC PURPOSE - Тюрікова, Олена; Жуков, Данило; Нестеренко, Діана (SWorldJournal, 2025)
The article addresses the issues of forming the first impression of the interior of cultural and pub-lic buildings based on the analysis of examples from global practices of designing public spaces. The tasks of the interior for specific purposes and the